2017
DOI: 10.1051/e3sconf/20172200092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental pollution with creosote oil or its vapors on biomass and selected physiological groups of microorganisms

Abstract: Abstract. Survival of microorganisms in soils from treatment facility and landfill of wooden railway sleepers contaminated with creosote oil as well as in two types of soils with different content of organic carbon, treated with creosote oil vapors, was assessed. Microbiological assays including determination of: the biomass of living microorganisms method and the number of proteolytic, lipolytic and amylolytic microorganisms were carried out under laboratory conditions. Chromatography analysis of the soil ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Contamination with petroleum derivatives, in particular, PAHs results in the need to search for various types of soil remediation. Our previous studies demonstrated the negative effect of coal tar creosote and volatile organic compounds emitted from wood treated with coal tar creosote on the activity of soil enzymes and the number of various microorganism groups [ 6 , 27 , 28 ]. The presented study results confirmed the degree of toxic effect of coal tar creosote on the microbiological and biochemical properties of soil.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination with petroleum derivatives, in particular, PAHs results in the need to search for various types of soil remediation. Our previous studies demonstrated the negative effect of coal tar creosote and volatile organic compounds emitted from wood treated with coal tar creosote on the activity of soil enzymes and the number of various microorganism groups [ 6 , 27 , 28 ]. The presented study results confirmed the degree of toxic effect of coal tar creosote on the microbiological and biochemical properties of soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transport and distribution of creosote within the environment depend on the physicochemical properties of its constituents [6][7][8]. In light of these facts, the chemicals in creosote can be transferred into animals and plants tissues posing a serious threat for humans [9][10][11][12] and implementation of new, environmentally friendly strategies of its removal is extremely important.…”
Section: Introductionmentioning
confidence: 99%